The Working Lives of New Writing Center Directors - Grutsch McKinney, Jackie; Jackson, Becky (Rebecca Lynn); Caswell, Nicole I. (Book collections on Project MUSE., 2016)
"Longitudinal qualitative studies that looks at the individual professional lives of nine new writing center directors' labor. The authors adopt case study and interview methodologies to examine the the labor these directors performed, as well as the labor they ignored, deferred, or sidelined temporarily"--Provided by publisher.